Tactile atimulation during the first year of child’s life - Woźniak, Martyna; Mazurkiewicz, Barbara; Dmoch-Gajzlerska, Ewa (Nursing in the 21st Century, 2011)
During recent years children’s care has changed and at present greater attention is given to the process of development, nursing and upbringing from the very first moments of a child’s life.Stimulation, the use of stimuli in a child’s development, is a long-lasting process which aims at helping to improve and perfect child’s development through conscious, systematic and integrated influence of home environment. Healthy children develop new skills and consolidate already achieved abilities due to the regular inflow of consciously defined stimuli. Some irregularities or the lack of some activities may constitute an obstacle to the process of learning new skills.The aim of this work is to define parents’ preparation to take up tactile stimulation during the first year of their child’s life.Material and method. The research in the form of questionnaires was conducted among 200 parents of children who finished the age of 6 months, but haven’t exceeded the age of 2 years yet. The research was conducted at the Town Day Nursery and outpatient clinics in Siedlce as well as at the Complex of Day Nurseries in the capital city – Warsaw, in the district of Śródmieście.The method used to gather the material was a diagnostic survey. The tool which was used during the conducted surveys was an independently constructed questionnaire. The questionnaire was consistent with methodological bases.Conclusions:• Parents should devote time and attention to their child in order to provide him/her with maximum basis of right development, especially during the first year of his/her life.• Tactile stimulation among young children allows to prepare them to form complex activities at further stages of their life.